Armadillo Ray - Beifuss, John, 1959-; Turley, Peggy; Antreasyan, Agustin (San Francisco : Chronicle Books, 1995)
Curious about the true nature of the moon, Armadillo Ray asks different animals for their opinion.
Keywords: Armadillos -- Fiction; Desert animals -- Fiction; Spanish language materials -- Fiction; Moon -- Fiction; Picture books; Fiction